Senegal : Third Review Under the Policy Support Instrument and First Review and Augmentation of Access Under the Exogenous Shocks Facility; Staff Report; Staff Supplement; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Senegal. (IMF Staff Country Reports; Country Report ;, 2009)
This paper presents key findings of the Third Review under the Policy Support Instrument (PSI) for Senegal. The budgetary slippages, which had seriously affected the economy and put Senegal's PSI-supported program at risk, have been successfully addressed. In line with program commitments, the government's unpaid bills have been substantially reduced and far-reaching public financial management reforms launched. A temporary fiscal easing relative to earlier program targets is envisaged for 2009 to help counter the impact of the external shock.